ST2 and IL‐33 polymorphisms and the development of childhood asthma: a prospective birth cohort study in Finnish children - Teräsjärvi, Johanna T.; Toivonen, Laura; Mertsola, Jussi; Peltola, Ville; He, Qiushui (APMIS : acta pathologica, microbiologica et immunologica Scandinavica, 2024)
The ST2/IL‐33 signaling pathway has an important role in the host inflammatory response. Here we aimed to study the association of ST2 and IL‐33 polymorphisms with serum soluble (s) ST2 and IL‐33 concentrations in healthy Finnish children and, in addition, their association with childhood asthma. In total, 146 children were followed from birth to the age 7 years for the development of asthma. Single‐nucleotide polymorphisms (SNPs) in ST2 and IL‐33 were determined, and associations of the SNP variants with serum levels of sST2 and IL‐33 at age of 13 months and with recurrent wheezing and childhood asthma at 7 years of age were analyzed. Children with ST2 rs1041973 AC/AA genotypes had significantly lower level of serum sST2 (2453 pg/mL; IQR 2265) than those with CC genotype (5437 pg/mL; IQR 2575; p = < 0.0001). Similar difference was also observed with ST2 rs13408661. No differences were observed between subjects with studied IL‐33 SNPs. Children who carried genetic variants of ST2 rs1041973 or rs13408661 seemed to have a higher risk of asthma. In contrast, children who carried genetic variants of IL‐33 rs12551268 were less often diagnosed with asthma. Even though these SNPs seemed to associate with asthma, the differences were not statistically significant.